The ATiK Learning Model with the Three-Period Lesson Technique and Self-Efficacy to Improve Early Childhood Numeracy Literacy - Putu Sri Darma Dewi; I Gede Astawan; Putu Aditya Antara (Indonesian Journal of Instruction, 2025)
The low level of numeracy literacy among early childhood learners in Indonesia presents a challenge in developing logical thinking and problem-solving skills from an early age. Improving numeracy literacy requires innovative learning approaches that also consider children's psychological aspects. This study aims to analyze the effects of the Amati, Tiru, Kerjakan (ATiK) learning model combined with the Three-Period Lesson technique and self-efficacy on early childhood numeracy literacy. The research employed a quasi-experimental design with a posttest-only control group. A total of 76 children participated as subjects, divided into experimental and control groups. Data were collected through observations and tests, using self-efficacy observation sheets and numeracy literacy test instruments. Data were analyzed using two-way ANOVA. The results indicate that the ATiK learning model with the Three-Period Lesson technique significantly enhances numeracy literacy. Self-efficacy also influences outcomes, with children who have high self-efficacy achieving better scores. A significant interaction was found between the learning model and self-efficacy. These findings highlight the importance of experiential learning and psychological reinforcement in early childhood education.